Puritanical Discourse in ‘Abd al-Hamīd al-Khatīb’s Nahj al-Burdah: Response to Excessive Praise of the Prophet - Rosalinda; Nurdin; Ilham, Andri (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
al-Madīḥ al-nabawī has traditionally been regarded as an expression of love for the Prophet Muhammad, encompassing accounts of his birth, miracles, praises, prayers, and hopes. However, recently, al-madīḥ al-nabawī has not only aimed to praise the Prophet but has also been transformed to serve the purpose of constructing specific discourses. Nahj al-Burdah by ‘Abd al-Ḥamīd, which includes praises of the Prophet, is suspected of containing the agenda of puritanism and criticism of religious practices deemed inconsistent with the Qur’an and Sunnah. This paper aims to uncover the discourse of puritanization in Nahj al-Burdah through Fairclough’s critical discourse analysis approach. The research reveals that Nahj al-Burdah contains puritanical discourse against excessive praise of the Prophet. This is demonstrated through the textual dimension containing ideological words and the discourse practice where the text is produced in the context of the Wahhabi reform movement to support what it believes as the purification of Islamic teachings and distributed by media and newspapers in Saudi Arabia to shape readers’ understanding of the importance of following the teachings of the salaf al-ṣāliḥ. Meanwhile, from a sociocultural practice perspective, Nahj al-Burdah serves as an effective tool for promoting puritanical discourse and reinforcing religious and political authority in Saudi Arabia during that period. al-Madīḥ al-nabawī selama ini hanya dianggap sebagai bentuk ekspresi kecintaan terhadap Nabi Muhammad yang memuat sejarah kelahiran, mukjizat, pujian, doa dan harapan. Namun, belakangan, al-madīḥ al-nabawī tidak saja bertujuan memuji Nabi tetapi juga ditransformasi untuk kepentingan membangun wacana tertentu. Nahj al-Burdah karya ‘Abd al-Ḥamīd yang memuat pujian kepada Nabi ditengarai memuat kepentingan wacana puritanisme dan kritik terhadap praktik keagamaan yang dianggapnya tidak sesuai dengan al-Qur’an dan Sunnah. Tulisan ini bertujuan mengungkap wacana puritanisasi dalam Nahj al-Burdah melalui pendekatan Analisis Wacana Kritis Norman Fairclough. Penelitian ini menunjukkan bahwa Nahj al-Burdah memuat wacana puritanisme terhadap pujian yang berlebihan kepada Nabi. Ini ditunjukkan melalui dimensi teks yang memuat kata-kata ideologis, discourse practice di mana teks diproduksi dalam konteks gerakan reformasi Wahhabi untuk mendukung pemurnian ajaran Islam dengan didistribusikan oleh media-media dan surat kabar di Saudi Arabia untuk dapat membentuk pemahaman pembaca tentang pentingnya mengikuti ajaran salaf al-ṣāliḥ. Sementara dari sociocultural practice, Nahj al-Burdah menjadi alat yang efektif dalam mempromosikan wacana puritanisme dan memperkuat otoritas religius serta politik di Arab Saudi pada masa itu.